2021
DOI: 10.1002/ajpa.24230
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability in the diet and feeding ecology of black‐and‐white ruffed lemurs (Varecia variegata) in Ranomafana National Park, southeastern Madagascar

Abstract: Objectives: We characterized the diet and foraging ecology of the black-and-white ruffed lemur (Varecia variegata), a specialized frugivore, and investigated behavioral strategies exhibited in response to seasonal changes in resource availability. Materials and Methods: Behavioral data were collected from the same two adjacent communities across 29 months during two observation periods (2007-2008; 2017-2018) in Mangevo, a primary rainforest habitat in southeastern Madagascar. To analyze feeding in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…To contribute to this goal, here we quantify the relationship between diet and the GM in Critically Endangered black-and-white ruffed lemurs ( Varecia variegata editorum ) occupying three habitats with different types and magnitudes of anthropogenic disturbance. Varecia are endemic to Madagascar’s eastern lowland and mid-altitude rain forests [ 38 , 39 ] and are considered obligate frugivores, consuming 75–99% fruit in pristine forest sites, though their degree of frugivory varies seasonally [ 40 – 44 ]. Given their selective feeding habits, Varecia are especially susceptible to anthropogenic pressure that often results in reduced fruit availability [ 42 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…To contribute to this goal, here we quantify the relationship between diet and the GM in Critically Endangered black-and-white ruffed lemurs ( Varecia variegata editorum ) occupying three habitats with different types and magnitudes of anthropogenic disturbance. Varecia are endemic to Madagascar’s eastern lowland and mid-altitude rain forests [ 38 , 39 ] and are considered obligate frugivores, consuming 75–99% fruit in pristine forest sites, though their degree of frugivory varies seasonally [ 40 – 44 ]. Given their selective feeding habits, Varecia are especially susceptible to anthropogenic pressure that often results in reduced fruit availability [ 42 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…At RNP, a primary location where aye-ayes and black-and-white ruffed lemurs are found, the peak of the wet season is typically January to March, while the peak of the dry season is typically June to October (Dunham et al, 2010). Food is most abundant from November to April and less abundant from May through October (Beeby & Baden, 2021). Thus, our measurements of hair growth rates taken in January and July in North Carolina corresponded with the mid-wet and mid-dry, abundant and lean seasons of Madagascar and especially RNP, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Ruffed lemurs (Genus Varecia ), found in Madagascar's eastern rainforests, are among the largest and most frugivorous of the living lemurs (Baden et al, 2008; Dew & Wright, 1998; Martinez & Razafindratsima, 2014; Razafindratsima et al, 2014; Vasey, 2006; Wright et al, 2011). Although they prefer fruits, they seasonally consume large quantities of flowers and fall back on leaves when other foods are not available (Balko, 1998; Beeby & Baden, 2021; Britt, 2000; Holmes et al, 2016). Despite their dietary breadth, ruffed lemurs exhibit several fruit‐specialist traits (Campbell et al, 2000; Edwards, 1995; Edwards & Ulrey, 1999), and have been shown to be highly susceptible to the effects of habitat degradation (White et al, 1995) and climate change (Morelli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their dietary breadth, ruffed lemurs exhibit several fruit‐specialist traits (Campbell et al, 2000; Edwards, 1995; Edwards & Ulrey, 1999), and have been shown to be highly susceptible to the effects of habitat degradation (White et al, 1995) and climate change (Morelli et al, 2020). Several studies have shown Varecia to alter their feeding behavior in response to changes in fruit availability resulting from both climatic seasonality and habitat disturbance (Balko, 1998; Balko & Underwood, 2005; Beeby & Baden, 2021; Britt, 2000; Holmes et al, 2016; Ratsimbazafy, 2002, 2006). Though one study examined the nutrient composition of dietary foods in one V. variegata population in eastern Madagascar (Schmidt et al, 2010), to date, there has been no exploration of nutrient intakes in this taxon.…”
Section: Introductionmentioning
confidence: 99%